Heterogeneous Crystal Nucleation from the Melt in Polyethylene Oxide Droplets on Graphite: Kinetics and Microscopic Structure - Muhammad Tariq; Thomas Thurn-Albrecht; Oleksandr Dolynchuk (Crystals, 2021)
It is well known that the crystallization of liquids often initiates at interfaces to foreign solid surfaces. In this study, using polarized light optical microscopy, atomic force microscopy (AFM), and wide-angle X-ray scattering (WAXS), we investigate the effect of substrate–material interactions on nucleation in an ensemble of polyethylene oxide (PEO) droplets on graphite and on amorphous polystyrene (PS). The optical microscopy measurements during cooling with a constant rate explicitly evidenced that the graphite substrate enhances the nucleation kinetics, as crystallization occurred at approximately an 11 °C higher temperature than on PS due to changes in the interactions at the solid interface. This observation allowed us to conclude that graphite induces heterogeneous nucleation in PEO. By employing the classical nucleation theory for analysis of the data with reference to the amorphous PS substrate, the obtained results indicated that the crystal nuclei with contact angles in the range of 100–117° were formed at the graphite interface. Furthermore, we show that heterogeneous nucleation led to a preferred orientation of PEO crystals on graphite, whereas PEO crystals on PS had isotropic orientation. The difference in crystal orientations on the two substrates was also confirmed with AFM, which showed only edge-on lamellae in PEO droplets on graphite compared to unoriented lamellae on PS.